Economics of imperfect information - Phlips, Louis (New York, 1988)
This book provides a systematic presentation of new microeconomic theories of imperfect information. Each chapter explores a particular type of informational asymmetry and reviews major papers. Wherever possible the theories are compared with experimental evidence. An extensive bibliography is included. Part I, statics, begins with an examination of how imperfect price or quantity information on the buyer's side provides new explanations of phenomena such as price dispersion and sales or resale price maintenance. A thorough discussion of private value auctions and common value auctions follows. Subsequent chapters investigate the links between uncertainty about personal characteristics and job signaling, incomplete insurance coverage, and credit rationing by banks. Part II, dynamics, relates the dynamics of collusion, predation, and market efficiency to the transmission, pooling, and aggregation of private information. Game theoretic findings and their implications for antitrust policy are included.
Keywords: Economic development